2015
DOI: 10.3765/salt.v24i0.2444
|View full text |Cite
|
Sign up to set email alerts
|

The grammar of discourse: The case of then

Abstract: This paper presents an analysis of then that appeals to discourse structure. I argue that then does not make any truth-conditional contribution but rather coordinates an anaphoric relation between consecutive discourse-moves. The meaning contribution of then is captured in terms of felicity conditions: then requires that two propositions enter into a 'causal explanatory claim'-relation in which one (the antecedent) provides the 'reasons' for the other (the consequent). This proposal targets then within conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Relatedly, it is felicitous to mark B's question in (6) with dann 'then' instead of denn, as shown in (i). We won't return to dann in this paper; seeBiezma (2014) for an analysis of the relevant use of English then. (i) [Same scenario as in (12).…”
mentioning
confidence: 99%
“…Relatedly, it is felicitous to mark B's question in (6) with dann 'then' instead of denn, as shown in (i). We won't return to dann in this paper; seeBiezma (2014) for an analysis of the relevant use of English then. (i) [Same scenario as in (12).…”
mentioning
confidence: 99%
“…The Relevance Effect reported in Skovgaard-Olsen et al (2016a) was found using indicative conditionals containing neither 'then' and 'will' in the consequent as stimulus materials. Consequently, it is possible that these results could be completely accounted for based on the meaning contribution of 'then' advanced in Iatridou (1994), von Fintel (1994, and Biezma (2014). Against such an account, it was found that the strong interaction for [if A, ¬C)], the Relevance factor, encoding the two different relevance levels, and of the Experiment factor (Exp1 vs. Exp2).…”
Section: Resultsmentioning
confidence: 99%
“…7 For all the experiments in this paper, 'then' in the consequents was removed from the contents. This is to see whether reason relation readings of conditionals are induced by 'then' in the consequents (as suggested by Iatridou, 1994;von Fintel, 1994;Biezma, 2014). Additionally, 'will' was removed.…”
Section: Llmentioning
confidence: 99%
See 2 more Smart Citations